2018 update of the APLAR recommendations for treatment of rheumatoid arthritis. (27th February 2019) - Lau, Chak Sing; Chia, Faith; Dans, Leonila; Harrison, Andrew; Hsieh, Tsu Yi; Jain, Rahul; Jung, Seung Min; Kishimoto, Mitsumasa; Kumar, Ashok; Leong, Khai Pang; Li, Zhanguo; Lichauco, Juan Javier; et al.
Abstract: Aim: To update recommendations based on current best evidence concerning the treatment of rheumatoid arthritis (RA), focusing particularly on the role of targeted therapies, to inform clinicians on new developments that will impact their current practice. Materials and methods: A search of relevant literature from 2014 to 2016 concerning targeted therapies in RA was conducted. The RA Update Working Group evaluated the evidence and proposed updated recommendations using the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach, to describe the quality of evidence and strength of recommendations. Recommendations were finalized through consensus using the Delphi technique. Results: This update provides 16 RA treatment recommendations based on current best evidence and expert clinical opinion. Recommendations 1‐3 deal with the use of conventional synthetic disease‐modifying antirheumatic drugs. The next three recommendations (4‐6) cover the need for screening and management of infections and comorbid conditions prior to starting targeted therapy, while the following seven recommendations focus on use of these agents. We address choice of targeted therapy, switch, tapering and discontinuation. The last three recommendations elaborate on targeted therapy for RA in special situations such as pregnancy, cancer, and major surgery. Conclusion: Rheumatoid arthritis remains a significant health problem in the Asia‐Pacific region. Patients with RA can benefit from the availability of effective targeted therapies, and these updated recommendations provide clinicians with guidance on their use.